Peran Edukator Perawat Dalam Meningkatkan Kepatuhan Pengobatan pada Lansia dengan Diabetes Melitus: The Role of Nurse Educators in Improving Treatment Compliance in Elderly Patients with Diabetes Mellitus - Narmawan, Narmawan; Abadi, Ellyani; Herman, Herman; Ditamaya, Firda Ayu Arisyanti (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Nurses as educators play a crucial role in educating patients about the importance of adherence in maintaining their health and improving their condition through care knowledge. The purpose of this study was to examine the relationship between the role of nurse educators and medication adherence in elderly people with diabetes mellitus. This study used a quantitative method with a cross-sectional correlational study design. The sample consisted of 59 elderly people with diabetes mellitus selected through purposive sampling. Data were collected using a questionnaire and analyzed using the Spearman correlation test. The results showed that the median score for the nurse educator role was 105, with a minimum score of 84 and a maximum of 107. Meanwhile, the median score for diabetes medication adherence was 5, with a score ranging from 2 to 6. The Spearman correlation test yielded a p-value of 0.001 and a correlation coefficient of 0.783. There is a significant positive relationship between the role of nurse educators and adherence to diabetes mellitus medication in elderly people. It is recommended that elderly people regularly follow their blood sugar check schedule, consult regularly, and involve family members in the treatment process to improve adherence.